2019
DOI: 10.3390/ijms21010202
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Pomegranate Juice against Parkinson’s Disease and Presence of Ellagitannins-Derived Metabolite—Urolithin A—In the Brain

Abstract: Pomegranate juice is a rich source of ellagitannins (ETs) believed to contribute to a wide range of pomegranate’s health benefits. While a lot of experimental studies have been devoted to Alzheimer disease and hypoxic-ischemic brain injury, our knowledge of pomegranate’s effects against Parkinson’s disease (PD) is very limited. It is suggested that its neuroprotective effects are mediated by ETs-derived metabolites—urolithins. In this study, we examined the capability of pomegranate juice for protection agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 69 publications
7
98
0
Order By: Relevance
“…These results support the development of functional foods for the prevention obesity, diabetes and dyslipidemias [32]. Studies with mice models have demonstrated that pomegranate juice exhibits a protective effect against oxidative damage in Parkinson's disease as well as antileishmanial activity [33,34].…”
Section: Juice Composition and Health Propertiessupporting
confidence: 57%
“…These results support the development of functional foods for the prevention obesity, diabetes and dyslipidemias [32]. Studies with mice models have demonstrated that pomegranate juice exhibits a protective effect against oxidative damage in Parkinson's disease as well as antileishmanial activity [33,34].…”
Section: Juice Composition and Health Propertiessupporting
confidence: 57%
“…Effect References fruit ↓of progression of cognitive and behavioral impairments in Alzheimer's disease [65] whole fruit extract anti-inflammatory and antioxidant effects [66] whole fruit extract ↓apoptosis and inflammation in liver cells [67] peel polysaccharide ↓weight loss and ↑immune organ index of immunosuppressed mice [68] peel polysaccharide protection against CCl 4 -induced liver injury [69] pomegranate aril extract inhibition of contact hypersensitivity of allergic dermatitis [70] juice ↑hypoxia-induced fetal growth and ↓apoptosis in the placenta in pregnant mice [71] juice neuroprotection and protection against oxidative damage in Parkinson's disease rat model [72] juice antileishmanial activity, probably by boosting the endogenous antioxidant activity in female BALB/c mice [73] leaf ↓total serum cholesterol and triglycerides of hyperlipidemic mice [74] peel extract contribution in prevention and treatment of Giardia lamblia infection [75] peel extract preventing bone loss associated with ovariectomy in mice [48] 3.2.1. Obesity, Diabetes…”
Section: Derivativementioning
confidence: 99%
“…Iran and India, but also America and the Mediterranean regions, are the main producers [ 33 , 34 ]. The demand for pomegranate keeps increasing year after year, also thanks to the increasing consumer awareness about the health benefits related to the pomegranate consumption, mainly in the form of juice [ 35 , 36 , 37 , 38 , 39 , 40 ]. Indeed, thanks to its high antioxidant capacity, pomegranate as a polyphenol-rich fruit is being commonly referred to as “superfruit” [ 28 , 41 ].…”
Section: Introductionmentioning
confidence: 99%